First Florida records for Anovia circumclusa (Gorham) (Coleoptera: Coccinellidae: Noviini): A natural enemy of Icerya genistae Hempel (Hemiptera: Margarodidae) - Forrester, Juanita A.; Vandenberg, Natalia J. (Zootaxa, 2008)
Lady beetles in the tribe Noviini (Coleoptera: Coccinellidae) are well-known control agents for scale insects. The tribe consists of ~ 80 species divided among three genera, and is represented on every continent except Antarctica. Anovia Casey is native to North and South America, Novius Mulsant is restricted to Australia, and Rodolia Mulsant, while native to Australia, has been widely introduced to other regions of the world.